No Future for our Children: Challenges faced by foreign minors living in South Africa - Willie, Ncumisa; Mfubu, Popo (African Human Mobility Review, 2021)
The intensification of international migration and continued conflicts in Africa have resulted in growing numbers of child migrants. Children are increasingly becoming mobile and crossing international borders unaccompanied. The movement of unaccompanied or separated minors triggers international obligations on all states that are party to the Convention of the Rights of a Child to take all available measures to ensure that children’s rights are respected, protected and fulfilled. South Africa has arguably the most progressive child protection mechanisms in Africa. Those mechanisms are conferred and extended to foreign minor children within its borders. However, due to a lack of coordination between the various state departments entrusted with matters concerning foreign minors, the state has failed to fulfil its duties as required by national and international law. This paper highlights the difficulties faced by foreign minors and how the gaps in law leave them undocumented, vulnerable and unable to access social services. This paper also discusses how South Africa’s approach to accompanied and unaccompanied foreign minor children provides no durable long term solutions for these children, effectively leaving them in a legal lacuna once they reach the age of majority. Drawing on our experience as refugee attorneys, we demonstrate that there are disparities between the law and the implementation of the law. We conclude with recommendations on possible policy and legislative reforms that can be implemented in order to ensure that South Africa develops a comprehensive and meaningful long-term approach for migrant children living in South Africa.